Characteristics of Pregnancy and Birth and Malignancy in the Offspring (Sweden) - Mogren, Ingrid; Damber, Lena; Tavelin, Björn; Högberg, Ulf (Cancer causes & control, 1999)
Objectives: The aim of the study was to investigate whether factors of pregnancy and birth influence the risk of malignancy in the offspring. Methods: Data on all deliveries (248,701 births) in two counties in Sweden 1955-90 were extracted from two birth registries. The follow-up period closed at the end of 1994 and the subjects were followed up to early middle-age at most (39 years). Incidence rates of malignancy were obtained from the Cancer Register 1958-1994. Standardized incidence ratios (SIR) and relative risks (RR) were calculated. Results: Overall, few associations were detected. A significantly increased standardized incidence ratio (SIR) of 50.00 (95% CI = 13.45-99.99) was found for the relationship between Down's syndrome and lymphatic leukaemia. Elder maternal age (≥35 years) and lymphatic leukaemia were associated with a significantly enhanced risk (SIR = 2.00; 95% CI, 1.16-3.20). Maternal age 25-34 years, compared to younger age, was associated with a reduced risk of cervical cancer (RR = 0.47; 95% CI = 0.26-0.86). Conclusions: Although some associations, the consistent pattern of non-association indicated a low impact of intrauterine environment or changed genetic material on the future development of malignancy in the offspring up to early middle-age.